2011
DOI: 10.1088/0953-8984/23/7/075501
|View full text |Cite
|
Sign up to set email alerts
|

Preserving the half-metallicity at the surfaces of rocksalt CaN and SrN and the interfaces of CaN/InN and SrN/GaP: a density functional study

Abstract: Recent theoretical studies indicate that metastable rocksalt CaN, SrN, and BaN exhibit half-metallic ferromagnetism (Volnianska and Boguslawski 2007 Phys. Rev. B 75 224418; Gao et al 2008 Phys. Lett. A 372 1512), and further experiments confirm the existence of self-assembled metastable CaN nanostructures (Liu et al 2008 Surf. Sci. 602 1844). We here use the first-principles method based on density functional theory to investigate the structural, electronic, and magnetic properties of the (111) surfaces of CaN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…First, it is necessary to define the correct arrangement of the atomic positions in the crystal [28,29]. In the half-Heusler C1 b structure, the XCaZ adopts three possible arrangements namely type (1), type (2), and type (3) as shown in Table 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…First, it is necessary to define the correct arrangement of the atomic positions in the crystal [28,29]. In the half-Heusler C1 b structure, the XCaZ adopts three possible arrangements namely type (1), type (2), and type (3) as shown in Table 1.…”
Section: Structural Propertiesmentioning
confidence: 99%
“…HM ferromagnets without transition metals have a small magnetic moment and may be more preferable in spintronic device applications because of their low stray fields and energy loss. There are several theoretical studies which predicted HM characteristic in ferromagnets without transition metals, such as, the graphene nanoribbon [35], the alkaline-earth carbides, and nitrides with zinc-blende and rocksalt structures [36][37][38][39][40][41]. Some studies have also confirmed the HM nature of these compounds, experimentally [42].…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, it is necessary to find HM compounds without transition metals which are called sp or d 0 half-metals. There are a few theoretical studies on d 0 ferromagnets such as the graphene nanoribbon [41], the alkaline-earth carbides, and the nitrides with zinc-blende and rock-salt structures [42][43][44][45][46][47] in which half-metallicity has been predicted. Experimental studies have also confirmed the HM nature for some of these compounds [48].…”
Section: Introductionmentioning
confidence: 99%